Pengaruh Teknologi Rekam Medis Manual Dan Rekam Medis Elektronik Terhadap Kepuasan Pasien Melalui Kecepatan Waktu Pelayanan Di Poliklinik Neurologi RSUD Pulang Pisau Pisau (Kalimatan Tengah) Tahun 2025 - Oktaviana Niken Prawitasari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of manual and electronic medical record technologies on patient satisfaction through service time efficiency at the Neurology Polyclinic of RSUD Pulang Pisau, Central Kalimantan. The background of this research stems from the issue of patient waiting times exceeding service standards, alongside the transition from manual to electronic systems that began in March 2023. This research employs a quantitative approach using descriptive and verification methods. The sample consists of 72 respondents selected through simple random sampling. Data were collected via questionnaires and analyzed using path analysis. The results indicate that electronic medical records significantly improve service speed and enhance patient satisfaction. Service time efficiency also serves as a mediating variable between medical record systems and patient satisfaction. These findings highlight the importance of digital transformation in healthcare services to improve efficiency and service quality, particularly in remote areas.